Luckiest girl alive eaudiobook A novel. - Knoll, Jessica (Simon & Schuster Audio, 2015)
*NOW A NETFLIX FILM STARRING MILA KUNIS* Fans of Gone Girl and The Girl on the Train will thrill at this "perfect page-turner" ( People )—that Reese Witherspoon describes as "one of those reads you just can't put down!" This "dark, twisty" ( Entertainment Weekly ), instant New York Times and USA TODAY bestselling novel follows an unforgettable young woman striving to create the perfect life—until a violent incident from her past threatens to unravel everything and expose her most shocking secret. HER PERFECT LIFE IS A PERFECT LIE As a teenager at the prestigious Bradley School, Ani FaNelli endured a shocking, public humiliation that left her desperate to reinvent herself. Now, with a glamorous job, expensive wardrobe, and handsome blue blood fiancé, she's this close to living the perfect life she's worked so hard to achieve. But Ani has a secret. There's something else buried in her past that still haunts her, something private and painful that threatens to bubble to the surface and destroy everything. With a singular voice and twists you won't see coming, Luckiest Girl Alive explores the unbearable pressure that so many women feel to "have it all" and introduces a heroine whose sharp edges and cutthroat ambition have been protecting a scandalous truth, and a heart that's bigger than it first appears. The question remains: will breaking her silence destroy all that she has worked for—or, will it at long last, set Ani free?